Production and physico-chemical properties analysis of co-pyrolytic oil derived from co-pyrolysis of scrap tires and sawdust - Hossain, S. (Taylor and Francis Ltd., 2021)
In this study, the co-pyrolysis of scrap tires and sawdust at different blend ratio was conducted in a fixed bed co-pyrolysis reactor. The main objective of this study was to investigate the effects of various mixing ratios of scrap tires and sawdust on the product yields. Moreover, the effects of co-pyrolysis temperature and feed size on the product yields were also studied. Results showed that optimal co-pyrolysis temperature, which provides maximum bio-oil yield was 450Â°C as well as optimal feed size was 2.36 mm. The maximum bio-oil yield 50Â wt was obtained for mixing ratio 4:1 of scrap tires and sawdust. The physico-chemical properties of various mixing ratio of scrap tires and sawdust were investigated and found higher calorific value for 4:1 blend ratio. It has been also compared with some conventional fuel in order to observe its suitability as an alternative fuel. Â© 2021 Taylor & Francis Group, LLC.